2019
DOI: 10.1080/15384101.2019.1642067
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Silencing of EPCAM suppresses hepatic fibrosis and hepatic stellate cell proliferation in mice with alcoholic hepatitis via the PI3K/Akt/mTOR signaling pathway

Abstract: Alcoholic hepatitis (AH) is a severe condition developed in patients with underlying alcoholic liver disease. Epithelial cell adhesion molecule (EPCAM) plays a role in hepatitis. Therefore, the current study aimed to explore the effect of EPCAM and its potential mechanism in AH. Bioinformatic analysis was performed to screen differentially expressed genes associated with AH. AH mouse models were established through a Lieber-DeCarli liquid diet containing 4% ethanol, which were co-treated with siRNA against EPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…And our data strongly indicated that RUT could partly participate in the palliation of the damage caused by ethanol though anti-apoptosis. The present findings also revealed that ethanol inhibited PI3K/ AKT pathway, which is consistent with previous literature (Zhang et al, 2019). In fact, the activation of PI3K/AKT pathway is essential for cell resistance to oxidation and apoptosis (Arab et al, 2019;Cao et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…And our data strongly indicated that RUT could partly participate in the palliation of the damage caused by ethanol though anti-apoptosis. The present findings also revealed that ethanol inhibited PI3K/ AKT pathway, which is consistent with previous literature (Zhang et al, 2019). In fact, the activation of PI3K/AKT pathway is essential for cell resistance to oxidation and apoptosis (Arab et al, 2019;Cao et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…et al, 2017 ), CXCL12 ( Semaan et al, 2017 ), and SENP2 ( Shen et al, 2012 ) were also reported to participate in the pathogenesis of liver cirrhosis and HCC. Zhang et al (2019) confirmed that silencing EPCAM can inhibit hepatic fibrosis and hepatic stellate cell proliferation in mice with alcoholic hepatitis through the PI3K/Akt/mTOR signaling pathway. Wenfang Tian et al (2016) also found that WDR5 is an important epigenetic factor in the process of liver fibrosis.…”
Section: Resultsmentioning
confidence: 64%
“…The JAK-STAT pathway is one of the most studied pathways in cell signal transduction and plays a variety of roles in physiological processes. 33 In addition, we found that caspase-3, which is associated with cell apoptosis, was upregulated after Rab40b knockdown. Therefore, the exact regulation between Rab40b and cleaved caspase-3 needs further investigation.…”
Section: Discussionmentioning
confidence: 77%